2019
DOI: 10.1177/1687814019841838
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of mobile phone distractions on pedestrian crossing behavior at signalized intersections: An observational study in China

Abstract: Nowadays phone distraction has started to become an increasingly recognized phenomenon. This article aims to examine the influences of phone use on pedestrian crossing behavior at signalized intersections in China. Using video recording and manual counting, pedestrian crossing behavior, age, gender, phone use, and waiting time are obtained at four signalized intersections. Totally, 4196 pedestrians are observed in four peak hours. Among them, 328 pedestrians (7.82%) are using their mobile phones, including 162… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Using mobile phones has a direct correlation with the incidence of unsafe behavior by pedestrians [7,25,26]. According to the results, mobile-phone use affected pedestrian precautionary behavior.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Using mobile phones has a direct correlation with the incidence of unsafe behavior by pedestrians [7,25,26]. According to the results, mobile-phone use affected pedestrian precautionary behavior.…”
Section: Discussionmentioning
confidence: 92%
“…In the study by Hatfield & Murphy (2007), they concluded that caution behavior was less common in men than in women, with this difference having been significant at signalized intersections for some passing behaviors, such as crossing the pedestrian signal, looking at the traffic while crossing, completing crossing at the marked pedestrian crossing, and conflict experiences (17). A large number of studies also indicate that men tend to show more risky behavior than women (7,24,26,27). Antic et al (2016) reported that men had a 4.1-time higher chance of showing at least one case of unsafe behavior when crossing the street than women (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially the latter has led to an increase in smartphonerelated accidents among pedestrians in recent years (Nasar and Troyer, 2013;Ren et al, 2021). Between 8 (Zhou et al, 2019) and 42% (Wells et al, 2018) of pedestrians were observed to cross the street while using a smartphone depending on the country and observation site, with most studies ranging from 20 to 30% (Vollrath et al, 2019;Solah et al, 2016;Horberry et al, 2019;Thompson et al, 2013;Piazza et al, 2020;Fernandez et al, 2020). Among all smartphone-related activities, a systematic review across 14 studies found that texting has the largest effects on pedestrians' behavior (Simmons et al, 2020).…”
Section: Introductionmentioning
confidence: 99%